Study the Efficiency of Poly Nicotine Amide as Anticorrosion Coating on Stainless Steel and Study Its Biological Activity - alkhfaji, sana adnan; I.Ali, Mayasa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Using an electrochemical polymerization technique at room temperature, poly nicotine amide (PNA) was produced from the monomer nicotine amide (NA) in aqueous solution. The structure of polymer layer generated on the stainless steel surface (316 L) (working electrode) is investigated by Fourier Transmission Infrared Region (FT-IR). The anti-corrosion activity of polymer coating on the stainless steel (SS 316 L) is investigated by electrochemical polarization in 0.20M solution of HCl at 293-323K. The graphene -modified polymer film-coated SS had greater protection efficiency (PE percent) when compared to Nano ZnO -modified polymer film-coated SS. For the corrosion process of SS 316 L, kinetic and thermo-dynamic parameters of activation are estimated. The antibacterial activity of coated film has been tested on both gram positive as well as gram negative bacteria by well diffusion approach, which include Staphylococcus aureus (Staph.Aure) and Ecoli. Through adding nanoparticles to a monomer solution to raise the effecincy of the polymer against the corrosion and bacterial, As a result, after modifying poly nicotine amide with nanomaterial, the inhibition zone values increased (Nano ZnO and Graphene).